If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -7 = 77 Reorder the terms: -7 + 7x = 77 Solving -7 + 7x = 77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7x = 77 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 77 + 7 7x = 77 + 7 Combine like terms: 77 + 7 = 84 7x = 84 Divide each side by '7'. x = 12 Simplifying x = 12
| 12b^3+39b^2-36b=0 | | 6a^2-13ab-5b^2=0 | | (x+7y)(3x-5y)=0 | | 3x+10+2x=0 | | a^4-49=0 | | 4y-11-7y=22-3 | | 20=3x-16+6 | | x=4(2x+4) | | 36z^2-81y^4=0 | | 24a^4+10a^3b-4a^2b^2=0 | | 3y^2+4y+2=0 | | (3x+5)(x-3)=5 | | 3(3x-5)=10x | | 10=9x | | 3x^4-9x^3-30x=0 | | 5x+3y=17 | | (13m+1)-(5m-4)= | | 16x^2-40x+25=0 | | (11m+1)-(3m-9)= | | x^3+2x^2=0 | | 2x^3-11x^2+18x-8= | | 64-x^2=0 | | 3x+27=12x-54 | | 4x+84=10x+12 | | 42+4y-8=17y-14-5y | | 6n^2-18n-13=0 | | 4x^2-48x+5=0 | | 36x^2-684x-648=0 | | 60-6x=3x+22 | | 3+9x=34+x | | -2y(3+4)=8y+12 | | 9+6(x-5)+(3x-8)=9x-29 |